Venous flow during manual lymphatic drainage applied to different regions of the lower extremity in people with and without chronic venous insufficiency: a cross-sectional study - Crisóstomo, Rute (2017)
OBJECTIVES: To evaluate the effect of manual lymphatic drainage (MLD) on venous flow when applied to the medial and lateral aspects of the thigh and leg in patients with chronic venous insufficiency (CVI) and healthy subjects. DESIGN: Cross-sectional study. SETTING: Participants were assessed in a school-based health community attendant service. PARTICIPANTS: Fifty-seven subjects participated in this study {mean age: 43 [standard deviation (SD) 14] years, 38 women and 19 men}. Of these, 28 subjects had CVI [mean age 47 (SD 12) years] and 29 subjects did not have CVI [mean age 39 (14) years]. INTERVENTION: MLD was applied by a certificated physical therapist to the medial and lateral aspects of the thigh and leg. MAIN OUTCOME MEASUREMENTS: Cross-sectional area; blood flow velocities in the femoral vein, great saphenous vein, popliteal vein and small saphenous vein at baseline and during MLD, measured by duplex ultrasound. RESULTS: Flow volume in the femoral vein increased from baseline [5.19 (SD 3.25)cm3/second] when MLD was applied to the medial [7.03 (SD 3.65)cm3/second; P≤0.001; mean difference -1.69; 95% confidence interval (CI) -2.42 to -0.97] and lateral [6.16 (SD 3.35)cm3/second; P≤0.001; mean difference -1.04; 95% CI -1.70 to -0.39] aspects of the thigh. Venous flow augmentation in the femoral vein and great saphenous vein was higher when MLD was applied to the medial aspect of the thigh (P<0.001), while MLD had a similar effect on venous blood flow regardless of whether it was applied to the medial or the lateral aspect of the leg (P=0.731). CONCLUSIONS: MLD increases blood flow in deep and superficial veins. MLD should be applied along the route of the venous vessels for improved venous return.